Direct allylation of in situ generated aldehyde acyl anions by synergistic NHC and palladium catalysis - Ahire, Milind M.; Mhaske, Santosh B. (Angewandte Chemie-International Edition, 2014)
The direct regioselective allylation of in situ generated aldehyde acyl anions has been achieved by synergistic NHC and Pd catalysis. It provides an efficient access to valuable beta,gamma-unsaturated ketones under mild reaction conditions starting from easily accessible allylic carbonates and aldehydes without any preactivation. The synergistic catalysis method demonstrated herein adds a new dimension to the area of metal-mediated C allylation.
Keywords: aldehyde umpolung; C allylation; N-heterocyclic carbenes; Palladium; synergistic catalysis

N-heterocyclic carbene (NHC)-catalyzed transformations for the synthesis of heterocycles - Das, Tamal Kanti; Biju, Akkattu T. (Progress in Heterocyclic Chemistry, 2020)
N-heterocyclic carbene (NHC)-based organocatalysis has been widely used for unconventional access to various target molecules. The use of chiral NHCs in the process results in the enantioselective synthesis of various heterocycles. The underlying principle of many of the NHC-catalyzed reactions is the remarkable ability of NHCs to reverse the normal mode of reactivity of aldehydes (umpolung). NHCs can catalyze transformations proceeding via the umpolung or nonumpolung mode for the synthesis of various functionalized molecules. The recent advances in the application of NHCs for the synthesis of various heterocyclic compounds are highlighted in this chapter.
Keywords: aldehyde umpolung; Aldimine umpolung; benzoin reaction; Breslow intermediates; Enantioselective synthesis; Heterocyclic synthesis; N-Heterocyclic carbene; Stetter reaction